Enhanced understanding of changes in tropical cyclones’ landfall frequency over mainland China - Li, Guangxin; Li, Qinglan; Zhao, Wei; Zhou, Guanbo; Qian, Qifeng; Qian, Chuanhai; He, Lunkai (Frontiers in Earth Science, 2022)
The climatological characteristics and interannual variations of tropical cyclones (TCs) making landfall in mainland China during the peak TC seasons (July-October) from 1980 to 2020 are examined using the China Meteorological Administration (CMA) best-track dataset. There were 270 TCs landfalling in mainland China during the study period, with 226 TCs landfalling in South China (SC) and 44 TCs landfalling in East China (EC). During 1980-2020, the number of TCs affecting mainland China decreases gradually, although the trend is not significant. The number of TCs impacting SC experiences a significant decrease, while the number of TC affecting EC is stable. Based on the change-point analysis, the TC landfall frequency in mainland China and SC incurred significant decreases in 1995/1996 and 1996/1997, respectively. The significant (insignificant) reduction in the number of landfalling TCs over SC (mainland China) is mainly due to the great reduction in the TC formation frequency over the western North Pacific (WNP). Meanwhile, the yearly mean of TCs’ landfalling latitudes moves northward slightly, possibly linked to the slight poleward shift of their genesis locations. A large area of negative anomalies in the lower-tropospheric absolute vorticity and positive variations in the vertical wind shear (VWS) over the tropical WNP are possibly responsible for the reduction in TC genesis over the WNP. Moreover, the apparent opposite anomalies of the two variables over the region north of "20°N" and south of "20°N" might contribute to the slight poleward shift of genesis locations of landfalling TCs during the 41 years. The variations in the large-scale steering flow are favorable for more TCs moving northwestward and making landfall in EC than before. Meanwhile, the decrease in TC landfall frequency over mainland China is found to be significantly correlated to the pronounced warming over the tropical Indian Ocean.